Analisis Penerapan Prinsip-Prinsip Desain, Tipografi, dan Warna pada Instagram Feed Senat Mahasiswa Universitas Negeri Medan Tahun 2019 - Anju Oktaviandri Permana; Fuad Erdansyah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the application of design principles, typography and color to the design of the 2019 Senat Mahasiswa Universitas Negeri Medan Instagram Feed which was analyzed by theoretical and empirical studies and then described and interpreted based on the research results. The population in this study were 15 designs for Instagram Feed Senat Mahasiswa Universitas Negeri Medan in 2019 then the research samples taken in this study were 5 designs using the Simple Random Sampling technique based on attractive design characteristics, compatibility between themes and colors in the design, and typographic characteristics. used in the design by setting aside things that are still less relevant to the population to be studied. The research method used is a qualitative method. The results of the research on this design were assessed by researchers and 3 raters who have described and interpreted the data tabulation and as for the results in the 2019 Senat Mahasiswa Universitas Negeri Medan Instagram Feed design research, it can be concluded that the quality of the application of design principles, typography and color as a whole is contained in Good category.